Product Development of Grilled Fish Cookies for Value Added from the Wang Rae Fish Rearing and Processing Group Community Enterprises, Phitsanulok Province - Samavardhana, Khamrop; Phrigboonchan, Pimchanok (Area Based Development Research Journal, 2021)
The locally processed fish products from Wang Rae fish farming and processing community enterprise, Chum Saeng Songkhram subdistrict, Bang Rakam district, Phitsanulok province was sold at low prices. This research aims to add value to locally processed fish products by innovating grilled fish cookies as new products. The participatory research consisting of three phases is employed. The first phase deals with the development of products from local raw materials, which involves several steps – determine the local identities, evaluate raw material properties, formulate the recipe and production process, evaluate shelf-life, and determine nutritional values. The second phase focuses on knowledge transfer and dissemination using practical training, which involves production process and production cost estimation. The third phase covers developing marketing plans and establishing market channels. The study reveals that grilled fish cookies products from local grilled fish were able to represent the local identity. The shelf-life evaluation shows that the products can be stored for 12 weeks at ambient temperature. The product qualities comply with the Thai Community Product Standard. The income generated from grilled fish cookies to the community enterprise is estimated to be over 75,000 Baht/month. The community learning center has been established at the community enterprise. Consequently, the community has gained awareness of local wisdom values as well as the importance of local product identity and benefited from career opportunities and higher income.